Nilai Multikultural Sikap Keberagamaan dalam Teks Puisi - Muliadi, Muliadi (Bahasa dan Seni: Jurnal Bahasa, Sastra, Seni, dan Pengajarannya, 2015)
The purpose of this research is to explain the values of multicultural attitudes toward diversity by utilizing poetry texts as the data source. The research employs a hermeneutic approach with several analytical models applied at the semantic, reflective, and existential levels of understanding. The results and discussion on attitudes toward religiosity indicate that: (1) devotion to God by an individual or a group should not be claimed as the only acceptable way of worshipping God; (2) self-control is an attitude that humans exercise in communicating with God; and (3) self-awareness or self-introspection can unite individuals regardless of their tribe, religion, or race.